La medicina ancestral como potencial turístico del área de influencia del Centro Binacional de Formación Técnica Zapotepamba, de la Universidad Nacional de Loja - Gallegos Tandazo, Melissa Isabela (2024)
Ancestral medicine is a practice that has been passed down from generation to generation, comprising knowledge, techniques and beliefs used to improve health. In the area of influence of the Centro Binacional de Formación Técnica Zapotepamba (CBFTZ), ancestral medicine is still alive and well. The general objective was to promote tourism development in the CBFTZ's area of influence through ancestral medicine, and two specific objectives: diagnose the current situation of ancestral medicine through files from the National Institute of Heritage and Culture, a survey to determine potential demand, a SWOT analysis and a strategy matrix. Second objective: to propose a tourism management model based on ancestral medicine. As a result, the study site has 9 ancestral doctors: herbalist, midwife, sobador and visionary, as well as the taxonomic classification of 56 medicinal plants, and 252 surveys applied to the Economically Active Population of the Olmedo, Catamayo and Celica cantons, and 4 key strategies were obtained from the SWOT matrix. Finally, objectives were established for areas of action based on ancestral medicine that will strengthen the tourism potential of the area under study. It is concluded that the use of this ancestral activity will contribute to the conservation of this ancestral knowledge in the future and will allow the diversification of the tourism offer to promote the local development of the area under study.